How to do things with ideas: Katharina Kraus on the regulative function of Kant’s Ideas of Reason - Hoffer, Noam (Con-Textos Kantianos. International Journal of Philosophy, 2025)
This paper offers a critical discussion of Katharina Kraus’s interpretation of Kant’s ideas of reason, as presented in her recent book. Kraus criticizes two opposing views, the ideas of reason as assumed noumenal entities or as mere heuristic fictions. While I share her dissatisfaction with these views, I suggest a more nuanced approach to them by emphasizing their normative grounds, especially in doctrinal non-evidential belief. As a solution to the problems of noumenalism and fictionalism, Kraus presents an elaborate perspectivalist reading of the ideas as serving a dual function: systematic structures for contexts of intelligibility and projected mind-independent normative standards for truth-evaluation. I raise questions about whether this account risks attributing a constitutive status to the ideas. I also suggest that the unique role of the idea of God is a regulative transformation of Kant’s pre-critical conception of God as the ground of the systematicity and necessity of the laws of nature. Building on Kraus’s insights, I propose an expressivist reading: the ideas of reason are meaningful not because they represent objects, hypothetical or fictional, but because they express the commitment to rational norms of inquiry. Because the ideas are expressions, they are grounded in reason’s norms of inquiry but are not constitutive of them.